Pyridine 2,4-Dicarboxylic Acid Suppresses Tomato Seedling Growth - Fragkostefanakis, Sotirios; Kaloudas, Dimitrios; Kalaitzis, Panagiotis (Frontiers in Chemistry, 2018)
Pyridine 2,4-dicarboxylic acid is a structural analogue of 2-oxoglutarate and is known to inhibit 2-oxoglutare-dependent dioxygenases. The effect of this inhibitor in tomato seedlings grown in MS media supplied with various concentrations of PDCA was investigated, resulting in shorter roots and hypocotyls in a dose-dependent manner. The partial inhibition of growth in roots was more drastic compared to hypocotyls and was attributed to a decrease in the elongation of root and hypocotyl cells. Concentrations of 100 and 250 μΜ of PDCA decreased hydroxyproline content in roots while only the 250 μΜ treatment reduced the hydroxyproline content in shoots. Seedlings treated with 100 μΜ PDCA exhibited enhanced growth of hypocotyl and cotyledon cells and higher hydroxyproline content resulting in cotyledons with greater surface area. However, no alterations in hypocotyl length were observed. Prolyl 4 hydroxylases (P4Hs) are involved in the O-glycosylation of AGPs and were also highly expressed during seedling growth. Moreover PDCA induced a decrease in the accumulation of HRGPs and particularly in AGPs-bound epitopes in a dose dependent-manner while more drastic reduction were observed in roots compared to shoots. In addition, bulged root epidermal cells were observed at the high concentration of 250 μΜ which is characteristic of root tissues with glycosylation defects. These results indicate that PDCA induced pleiotropic effects during seedling growth while further studies are required to better investigate the physiological significance of this 2-oxoglutarate analogue. This pharmacological approach might be used as a tool to better understand the physiological significance of HRGPs and probably P4Hs in various growth and developmental programs in plants.